1993
DOI: 10.1002/aja.1001980305
|View full text |Cite
|
Sign up to set email alerts
|

Spatio‐temporal distribution of acidic and basic FGF indicates a role for FGF in rat lens morphogenesis

Abstract: As part of an investigation into the role FGF in lens development, we have studied the distribution of both aFGF and bFGF during eye morphogenesis from embryonic days 10 to 18 (E10–E18) in the rat. For aFGF, reactivity was found only in ectoderm at E10, prior to contact between the optic vesicle and presumptive lens ectoderm. During lens placode formation (E11) there was a transient, diffuse reactivity for aFGF in anterior optic vesicle cells directly apposed to the labelled ectoderm of the lens placode. At E1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(32 citation statements)
references
References 38 publications
(43 reference statements)
1
31
0
Order By: Relevance
“…Since several different FGFs are expressed in the developing eye-in the presumptive lens ectoderm and the optic stalk, as well as in the developing ciliary epithelium-it is likely that some redundancy exists in this system (see de Iongh and McAvoy, 1993;McCabe et al, 1999, for review;Vogel-Hopker et al, 2000). Thus, it has been difficult to demonstrate a requirement for FGF in the development of the neural retinal fate.…”
Section: Bc) (See Alsomentioning
confidence: 99%
“…Since several different FGFs are expressed in the developing eye-in the presumptive lens ectoderm and the optic stalk, as well as in the developing ciliary epithelium-it is likely that some redundancy exists in this system (see de Iongh and McAvoy, 1993;McCabe et al, 1999, for review;Vogel-Hopker et al, 2000). Thus, it has been difficult to demonstrate a requirement for FGF in the development of the neural retinal fate.…”
Section: Bc) (See Alsomentioning
confidence: 99%
“…Based on previous reports of FGF expression patterns, we extended our analysis to FGF1,2,3,5,8,9 and 15 to assay their pairwise interactions with FGFR1b, 1c, 2b, 2c, 3b, 3c and 4 (Chow and Lang, 2001;de Iongh and McAvoy, 1993;Kitaoka et al, 1994;Lovicu and Overbeek, 1998;Martinez-Morales et al, 2005;McWhirter et al, 1997;Nguyen and Arnheiter, 2000;Vogel-Hopker et al, 2000;Zhao et al, 2001). This includes all the FGF and FGFR variants known to be present during early eye development.…”
Section: Ndst1 Mutants Are Defective In Heparan Sulfate Synthesis Andmentioning
confidence: 99%
“…The formation of these cells types, and their correct proportionality, is necessary for the proper function of the vertebrate eye. FGF molecules and their receptors are expressed in developing retina (de Iongh and McAvoy, 1993;Gao and Hollyfield, 1995;McFarlane et al, 1998;Patstone et al, 1993), and several studies have investigated their role in proliferation, survival and differentiation of retinal cells (Guillemot and Cepko, 1992;Park and Hollenberg, 1989;Sievers et al, 1987). It was shown that inhibition of the FGFR1-mediated pathway in Xenopus embryos resulted in a 50% loss of photoreceptor and amacrine cells, with a concomitant increase of Müller cells (McFarlane et al, 1998).…”
Section: Introductionmentioning
confidence: 99%